CRITERIA FOR THE FEASIBILITY OF INVESTING IN THE PRODUCTION OF NEW GOODS FOR THE PERSPECTIVE OF MODERNIZATION OF THE ECONOMY - Soliar, Viktoriia; Radchenko, Liubov; Sahetgylydgov, Nuriagdy (SWorld-Ger Conference proceedings, 2023)
The article substantiates the expediency of using key indicators for assessing the effectiveness of investment projects for the production of new products, their sequence and interrelationship. In the main part of the research, it is proved that the appli